No association between mitochondrial DNA copy number and colorectal adenomas. Issue 8 (10th August 2015) - Thyagarajan, Bharat; Guan, Weihua; Fedirko, Veronika; Barcelo, Helene; Tu, Huakang; Gross, Myron; Goodman, Michael; Bostick, Roberd M.
Abstract : Despite previously reported associations between peripheral blood mtDNA copy number and colorectal cancer, it remains unclear whether altered mtDNA copy number in peripheral blood is a risk factor for colorectal cancer or a biomarker for undiagnosed colorectal cancer. Though colorectal adenomas are well‐recognized precursor lesions to colorectal cancer, no study has evaluated an association between mtDNA copy number and colorectal adenoma risk. Hence, we investigated an association between peripheral blood mtDNA copy number and incident, sporadic colorectal adenoma in 412 colorectal adenoma cases and 526 cancer‐free controls pooled from three colonoscopy‐based case–control studies that used identical methods for case ascertainment, risk factor determination, and biospecimen collection. We also evaluated associations between relative mtDNA copy number and markers of oxidative stress, including circulating F2 ‐isoprostanes, carotenoids, and fluorescent oxidation products. We measured mtDNA copy number using a quantitative real time polymerase chain reaction (PCR). We used unconditional logistic regression to analyze the association between mtDNA copy number and colorectal adenoma risk after multivariable adjustment. We found no association between logarithmically transformed relative mtDNA copy number, analyzed as a continuous variable, and colorectal adenoma risk (odds ratio = 1.02, 95%CI: 0.82–1.27; P = 0.86). There were no statistically significant associations between relative mtDNA copy number and other markers of oxidative stress. Our findings, taken together with those from previous studies, suggest that relative mtDNA copy number in peripheral blood may more likely be a marker of early colorectal cancer than of risk for the disease or of in vivo oxidative stress. © 2015 Wiley Periodicals, Inc.